2021
DOI: 10.1093/rheumatology/keab681
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold capillaries and myositis-specific antibodies in anti–melanoma differentiation–associated gene 5 antibody-positive dermatomyositis

Abstract: Objectives This study aimed to quantify nailfold capillary (NFC) abnormalities in anti-melanoma differentiation-associated gene 5 (MDA5)-positive dermatomyositis (DM) patients and to evaluate the association with clinical parameters, including serum biomarkers. In addition, we aimed to clarify the period leading to remission of NFC abnormalities during immunosuppressive treatment in patients with DM. Methods A prospective obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Moreover, according to the MSAs classification, we found that the expression of CTACK, Eotaxin, IL1Rα, IL7, IL18, IP10, MCP1, MCP3, MCSF, MIG and SCGFβ were differentially expressed in anti-ARS positive, anti-MDA5 positive, anti-TIF1γ positive IIMs compared with HC groups. These results were partially consistent with those of previous reports ( Gono et al, 2010 ; Gono et al, 2014 ; Zou et al, 2016 ; Chen et al, 2018 ; Bai et al, 2020 ; Sugimoto et al, 2021 ). In addition, serum SCGFβ and CTACK were first found to be increased in IIMs and anti-MDA5 positive patients, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, according to the MSAs classification, we found that the expression of CTACK, Eotaxin, IL1Rα, IL7, IL18, IP10, MCP1, MCP3, MCSF, MIG and SCGFβ were differentially expressed in anti-ARS positive, anti-MDA5 positive, anti-TIF1γ positive IIMs compared with HC groups. These results were partially consistent with those of previous reports ( Gono et al, 2010 ; Gono et al, 2014 ; Zou et al, 2016 ; Chen et al, 2018 ; Bai et al, 2020 ; Sugimoto et al, 2021 ). In addition, serum SCGFβ and CTACK were first found to be increased in IIMs and anti-MDA5 positive patients, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies also showed that there are inverse correlations between NVC scores and disease activity before treatment (n = 10) and that the density can Reumatologia 2022; 60/1 be a dynamic marker of global disease activity in adult patients (n = 15) with DM that can be improved after treatment [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The capillaroscopy parameters were evaluated by stereomicroscopy in power of × 250: distribution, morphology of capillaries, dimensions based on the largest diameter of the apical side (dilated > 20 μm, giant > 50 μm), capillary length (normal or elongated: ≥ 300 μm), mean capillary density (low density was defined as reduction of the normal number of the capillaries below 7 per linear millimetre), avascular area (intercapillary distance > 500 μm), and microhaemorrhages [13,14], based on the last standardization of NFC and International Delphi consensus for reporting the data (2020).…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that the vascular abnormalities in the study by Matsuda et al [ 1 ] were mild and could be improved to almost normal. We have previously reported that even in patients with SLE and DM, nailfold capillary abnormalities can be improved by drug therapy without the use of antifibrotic drugs [ 5 , 6 , 7 ]. We believe that further verification is needed to determine whether nintedanib improves nailfold capillary abnormalities.…”
mentioning
confidence: 99%